2002
DOI: 10.1007/3-540-47922-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Two-Literal Logic Programs and Satisfiability Representation of Stable Models: A Comparison

Abstract: Logic programming with the stable model semantics has been proposed as a constraint programming paradigm for solving constraint satisfaction and other combinatorial problems. In such a language one writes function-free logic programs with negation. Such a program is instantiated to a ground program from which the stable models are computed. In this paper, we identify a class of logic programs for which the current techniques in solving SAT problems can be adopted for the computation of stable models efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…However, the problem becomes interesting when we drop the requirement of modularity. In the special case when all rules in a program have at most one literal in their bodies (so-called 2-literal programs), Huang et al [8] showed that there is an efficient translation to sets of clauses that do not need to use any extra variables. They also observed that many of the logic programs in answer set programming applications are essentially 2-literal ones.…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem becomes interesting when we drop the requirement of modularity. In the special case when all rules in a program have at most one literal in their bodies (so-called 2-literal programs), Huang et al [8] showed that there is an efficient translation to sets of clauses that do not need to use any extra variables. They also observed that many of the logic programs in answer set programming applications are essentially 2-literal ones.…”
Section: Introductionmentioning
confidence: 99%
“…there is a rule of the form (12) in P , such that u = hd(r), and either v or not v ∈ lit(W (A i )), for some i (1 ≤ i ≤ n). …”
Section: Loop Formulasmentioning
confidence: 99%
“…Only when a model of completion is generated which fails to be a stable model, the loop formula for a loop that caused the failure is constructed. In many cases, loop formulas need not be constructed at all [12]. In contrast, ranking constraints are introduced for rules in a given program, no matter whether there actually exist loops or not, or whether a loop contributes to the generation of a model of completion which is not a stable model.…”
Section: ⊓ ⊔mentioning
confidence: 99%
“…(2) Many important NP-complete problems can be easily encoded as (negative) two-literal programs (Huang et al 2002). (3) Negative two-literal programs allow us to conduct large scale experiments with existing ASP solvers, such as smodels, dlv and clasp.…”
Section: Introductionmentioning
confidence: 99%